Nine common errors in the application of mobile technology in libraries - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2013)
Libraries are trying out mobile technologies and looking for applications of smartphones and tablets that can improve library services and professional practice. Through the analysis of the first experiences, professional literature and direct contact with professionals, some common errors have been detected. They are listed and explained in this text in order to serve as a starting point for professional discussion and reflection.
Keywords: Mobile devices; Smartphones; Tablets; Mobile web; Augmented reality; QR codes; Apps; Libraries.